Evaluation of microbial potential, sensory and nutritional quality of mangoes following gamma irradiation - Abdullah, Roheena; Suman, Maryam; Naz, Shagufta; Iqtedar, Mehwish; Kaleem, Afshan; Aftab, Mahwish (Progress in Nutrition, 2018)
Foodborne diseases pose a widespread threat to human health and they are an important cause of reduced economic productivity. The postharvest diseases are considered worldwide as the major issue for postharvest facilities. Although there are various methods to decrease postharvest losses, consumers are looking for agricultural product free of chemicals. In the present study impact of gamma radiations on microflora, sensory and nutritional quality of mango cultivar chaunsa was evaluated. The samples was subjected to various irradiation doses (0.25, 0.5 and 1.25) and stored at refrigerated temperature. Sensory, microbiological and proximate analysis was estimated on weekly intervals for the treated and control samples. The microbial flora eliminated to maximum extent at dose 0.5 kGy without any significant change in sensory properties. However, prominent sensory changes were observed at dose >1 kGy. Proximate analysis showed 0.5kGy does not cause any significant changes in moisture, ash, fat, fiber and protein content. So, 0.5kGy was found optimum for chaunsa that increase the shelf-life up to 7 days without causing any damage to fruit.